Respostas
respondido por:
0
{4x + y = 14
{ x - y = 16
Fazendo pelo método da adição
{4x + y = 14
{ x - y = 16
----------------
5x = 30
x = 30/5
x = 6
Substituindo x na equação mais fácil
x - y = 16
6 - y = 16
6 - 16 = y
y = -10
{ x - y = 16
Fazendo pelo método da adição
{4x + y = 14
{ x - y = 16
----------------
5x = 30
x = 30/5
x = 6
Substituindo x na equação mais fácil
x - y = 16
6 - y = 16
6 - 16 = y
y = -10
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás